2006
DOI: 10.1193/1.2201971
|View full text |Cite
|
Sign up to set email alerts
|

Coastal Ecosystems and Tsunami Protection after the December 2004 Indian Ocean Tsunami

Abstract: An exploratory study was conducted on the role of coastal ecosystems in protecting communities from the December 2004 Indian Ocean tsunami, focusing on mangrove forests on the Andaman coast of Thailand and how well villages were undertaking environmental conservation. Remote sensing analysis identified predisaster mangrove change and postdisaster structural damage and landscape changes. Field data from five sites (20 villages), gathered via the VIEWS™ data collection system, validated and supplemented this ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…There has also been investment in post-tsunami development projects involving restoration of natural systems, including mangroves, in expectation of shoreline protection benefit (IUCN, 2006a). Some studies have suggested that villages behind mangroves and other coastal vegetation were better protected than those in more exposed locations (Danielsen et al, 2005;Kathiresan and Rajendran, 2005;Chang et al, 2006;Ranasinghe and Kallesoe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…There has also been investment in post-tsunami development projects involving restoration of natural systems, including mangroves, in expectation of shoreline protection benefit (IUCN, 2006a). Some studies have suggested that villages behind mangroves and other coastal vegetation were better protected than those in more exposed locations (Danielsen et al, 2005;Kathiresan and Rajendran, 2005;Chang et al, 2006;Ranasinghe and Kallesoe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Post-tsunami field studies have supported these accounts, suggesting that villages behind coastal systems (i.e., mangroves, reefs and dunes) were better protected than those in more exposed locations (Danielsen et al 2005, Kathiresan and Rajendran 2005, Chang et al 2006, Ranasinghe and Kallesoe 2006 and that the aerial root system of mangroves increased drag force and trapped floating objects (Tanaka et al 2007). Additionally, simulated experiments and some theoretical models have concluded a protective value for coastal forests (Harada et al 2002, Irtem et al 2009).…”
Section: Introductionmentioning
confidence: 68%
“…This is based upon models using data on human deaths and tsunami inundation (in terms of both presence and distance). Second, we compare our findings with existing modelling studies, based upon inundation distance of the tsunami wave as the measure of impact (Adams et al 2005, Chatenoux and Peduzzi 2005, Chang et al 2006, Iverson and Prasad 2007. Our study v www.esajournals.org concludes by considering the relevance of tsunami related issues and wider environmental concerns to coastal policy setting in Sri Lanka.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The 2004 tsunami impacted coastal areas of the Andaman Sea coast and the Bay of Bengal. Several studies were conducted dealing with the assessment of tsunami impacts to shorelines and the role of coastal vegetation in protecting local communities 11,12 . As specific examples in this region, Pandanus odoratissimus L.f. and C. equisetifolia mitigated destructive tsunami forces, their effectiveness depending on the magnitude of the tsunami and vegetation structure 13 .…”
Section: Introductionmentioning
confidence: 99%